2021
DOI: 10.3390/antiox10020220
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-Based Therapies in Male Infertility: Do We Have Sufficient Evidence Supporting Their Effectiveness?

Abstract: Under physiological conditions, reactive oxygen species (ROS) play pivotal roles in various processes of human spermatozoa. Indeed, semen requires the intervention of ROS to accomplish different stages of its maturation. However, ROS overproduction is a well-documented phenomenon occurring in the semen of infertile males, potentially causing permanent oxidative damages to a vast number of biological molecules (proteins, nucleic acids, polyunsaturated fatty acids of biological membrane lipids), negatively affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 183 publications
0
15
0
1
Order By: Relevance
“…As spermatozoa are characterized by an extremely high susceptibility to oxidative damage, seminal plasma released from accessory glands contains an abundant antioxidant system, which includes both enzymatic and nonenzymatic factors for effectively protecting spermatozoa against ROS attack. In this context, sperm cells are highly dependent on the powerful antioxidant properties of the surrounding environment [ 34 ]. Our previous report demonstrated that a redox imbalance in semen occurred in men exposed to prolonged environmental (professional drivers) or clinically recognized local hyperthermia (varicocele).…”
Section: Discussionmentioning
confidence: 99%
“…As spermatozoa are characterized by an extremely high susceptibility to oxidative damage, seminal plasma released from accessory glands contains an abundant antioxidant system, which includes both enzymatic and nonenzymatic factors for effectively protecting spermatozoa against ROS attack. In this context, sperm cells are highly dependent on the powerful antioxidant properties of the surrounding environment [ 34 ]. Our previous report demonstrated that a redox imbalance in semen occurred in men exposed to prolonged environmental (professional drivers) or clinically recognized local hyperthermia (varicocele).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the aforementioned embryological data showing the effectiveness of the antioxidant supplementation taken by males, we chose pregnancy as the primary endpoint, since we believe it is a better marker of improved fertility potential. A recent analysis of the literature of the last ten years concerning the effects of low molecular weight antioxidants (ascorbic acid, N-acetylcysteine, alpha-tocopherol, and CoQ10, administered as a single antioxidant or as a combination of different antioxidants plus vitamins and/or micronutrients) showed that only ten studies included pregnancy and/or live birth rates as an outcome measure to determine the effects of the therapy [ 27 ]. Unfortunately, only two reports found improvement of the pregnancy rate in the group of antioxidant-treated patients in scientifically rigorous case–control studies [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oxidative stress could be considered a fundamental parameter of the semen and marker of sperm quality [81]. Indeed, in recent years, numerous studies have found a correlation between ROS overproduction and idiopathic infertility [82,83]. Exposure to antioxidants has positive consequences on all parameters and improves the spermatozoa performance even after the freeze-thaw cycle.…”
Section: Discussionmentioning
confidence: 99%